Characterization of a thermostable extracellular tannase produced under submerged fermentation by Aspergillus ochraceus - Goncalves, Heloisa Bressan [UNESP]; Riul, Alana Jacomini [UNESP]; Quiapim, Andrea Carla; Jorge, Joao Atilio; Souza Guimaraes, Luis Henrique (Universidade Católica de Valparaíso, 2012)
Background: Tannases are enzymes that may be used in different industrial sectors as, for example, food and pharmaceutical. They are obtained mainly from microorganisms, as filamentous fungi. However, the diversity of fungi stays poorly explored for tannase production. In this article, Aspergillus ochraceus is presented as a new source of tannase with interesting features for biotechnological applications. Results: Extracellular tannase production was induced when the fungus was cultured in Khanna medium with tannic acid as carbon source. The extracellular tannase was purified 9-fold with 2% recovery and a single band corresponding to 85 kDa was observed in SDS-PAGE. The native apparent molecular mass was estimated as 112 kDa. Optima of temperature and pH were 40 degrees C and 5.0, respectively. The enzyme was fully stable from 40 degrees C to 60 degrees C during 1 hr. The activity was enhanced by Mn2+ (33-39%) and NH4+ (15%). The purified tannase hydrolyzed tannic acid and methyl gallate with Km of 0.76 mM and 0.72 mM, respectively, and Vmax of 0.92 U/mg protein and 0.68 U/mg protein, respectively. The analysis of a partial sequence of the tannase encoding gene showed an open read frame of 567 bp and a sequence of 199 amino acids were predicted. TLC analysis revealed the presence of gallic acid as a tannic acid hydrolysis product. Conclusion: The extracellular tannase produced by A. ochraceus showed distinctive characteristics such as monomeric structure and activation by Mn2+, suggesting a new kind of fungal tannases with biotechnological potential. Further, it was the first time that a partial gene sequence for A. ochraceus tannase was described.
Keywords: Aspergillus ochraceus; gallic acid; tannase; tannic acid; tannin acyl hydrolase